Governance for Social Purpose: Negotiating Complex Governance Practice - Carroll, Brigid Jan; Fouche, Christa; Curtin, Jennifer (Frontiers in Psychology, 2020)
Social purpose initiatives rarely take place in one sector or policy domain. They are likely to cross sector, community, local, national and indigenous boundaries and, in so doing, require alternative governance arrangements that are responsive and sustainable. This article focuses on the process of forging cross boundary governance processes drawing on a case study characterised by complex cross sector demands. The subject of the case study is a paradigm-breaking primary health and well-being initiative for a region of New Zealand with longstanding healthcare challenges but contemporary possibilities. We were invited by the owners of this initiative to record and reflect on the challenges and successes, and from this to identify what might be possible for future innovations. In doing so we draw on the adaptive governance literature to frame the governance challenges and offer five paradoxes requiring collective navigation. We recognise the importance of our need to engage with Indigenous scholarship in future analyses and conclude with a series of recommendations on how such paradoxes are navigated for those needing to build governance practice in innovative social purpose initiatives.